Executive functioning in adults with attention deficit hyperactivity disorder: A systematic review - Carlos Francisco Rincón; Lady Bernal Morales; Sheylla Tello Sandoval (Acta Neurológica Colombiana, 2024)
Introduction: Executive function deficits are associated with attention deficit hyperactivity disorder (ADHD) in both children and adults. The inattentive subtype is primary related to “cold” executive functions, while the hyperactive subtype is related to “warm” executive functions.